High-adhesion water-based ink and preparation process thereof

By adding porous cellulose to the aqueous ink, using its hydrophilicity and negative charge characteristics to form a hydrogen bond network and a physical chimeric structure, the problem of poor adhesion performance of water-based ink is solved, and the high adhesion and peel resistance are improved, meeting the quality requirements of high-end product packaging and printing.

CN119684843AActive Publication Date: 2025-03-25HANGZHOU LINAN SHENGHENG DECORATION MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411849402.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The adhesion performance of existing water-based inks on substrates is poor, and the internal adhesion is difficult to effectively characterize, making it difficult to meet quality requirements in the packaging and printing of some high-end products.

Method used

By adding porous cellulose to the aqueous ink, it uses its good hydrophilicity and negative charge characteristics to form a hydrogen bond network and a physical chimeric structure, and improves the connection tightness and anti-peeling properties of the paint film.

Benefits of technology

It significantly improves the adhesion of water-based inks, including substrate adhesion and internal adhesion, and meets the quality requirements of high-end product packaging and printing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684843A_ABST
    Figure CN119684843A_ABST
Patent Text Reader

Abstract

The invention relates to water-based ink with high adhesive force and a preparation process thereof, and the water-based ink at least comprises the following raw materials in parts by mass: 100-140 parts of acrylic emulsion; 120 to 160 parts of titanium dioxide; 20 to 60 parts of ethylene glycol; 0-5 parts of a functional auxiliary agent; 80 to 100 parts of an organic pigment; 400 to 600 parts of deionized water; the addition mass of the porous cellulose is 0.08-0.16 times of the sum of the mass of the acrylic emulsion and the mass of the titanium dioxide, and the Zeta potential of the porous cellulose is not greater than-45mV when the pH value is equal to 7; the porous cellulose is obtained by dissolving cellulose diacetate, curing, splitting phases and hydrolyzing and regenerating in a hydrolysis bath, the hydrolysis bath is an aqueous solution of sodium hydroxide and a potential regulator, and the potential regulator is at least one of triethylamine, diethylamine and ammonia water. The water-based ink disclosed by the invention not only has good adhesive force with a printing substrate, but also has good adhesive force inside.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of water-based inks, and in particular to a water-based ink with high adhesion and a preparation process thereof. Background Art

[0002] With the continuous advancement of printing technology and the enhancement of environmental awareness, traditional solvent-based inks have gradually failed to meet the requirements of modern society for environmental protection and sustainable development due to their large amount of volatile organic compounds (VOCs), which pose a potential threat to the environment and human health. Therefore, the development of environmentally friendly inks has become an important development direction for the printing industry.

[0003] Water-based inks, because they do not contain volatile organic solvents, greatly reduce VOCs emissions, thereby reducing air pollution, improving the environment for printing operators, and benefiting the health of workers. It can completely eliminate certain toxic and harmful substances in solvent-based inks, eliminate harm to the human body and pollution to packaged goods, improve the overall environmental quality, and is particularly suitable for packaging and printing products with strict hygienic requirements such as tobacco, alcohol, food, beverages, medicines, and children's toys. In addition, it can not only reduce the risk and hidden dangers of fire caused by static electricity and flammable solvents, but also reduce the toxicity of the printed surface and facilitate the cleaning of printing equipment.

[0004] As an environmentally friendly ink, water-based ink has gradually attracted market attention for its advantages such as low VOCs emission, good printing adaptability and color reproducibility. Water-based ink is mainly composed of water-soluble resin, pigment, water, additives, etc. In the printing process, water is used as a solvent or diluent, which effectively reduces pollution to the environment.

[0005] However, there are still some technical challenges in the practical application of water-based inks. Whether it is imported water-based inks or domestic water-based inks, the printing performance and quality cannot meet the standards of solvent-based gravure inks. At present, water-based inks have the disadvantages of not being resistant to alkali, ethanol and water, drying slowly, having poor glossiness, and easily causing paper shrinkage. This is mainly due to the high surface tension of water (72dyne / cm), which makes the ink difficult to wet and dries slowly.

[0006] For example, the adhesion performance of water-based ink on the substrate is often worse than that of solvent-based ink. Therefore, it is generally necessary to refer to the national standard to test the adhesion performance of water-based ink. For example, GB / T 13217.7-2023 Ink Adhesion Test Method records the standards for measuring the adhesion of various inks on substrates such as plastic film, aluminum box, tinplate, paper, etc. Since the tape peeling method is simple to operate, it is more commonly used. Its principle is that the ink film of the special printing substrate of different system inks that has been treated is adhered to or damaged by the tape, and the ink adhesion is expressed as the ink film intact rate, expressed in %. Since its test results need to be covered with a certain size of translucent millimeter grid paper on the peeled part, the number of grids occupied by the ink film and the number of grids occupied by the peeled ink layer are counted, and the ink adhesion data can be calculated.

[0007] The above test method can indeed well characterize the adhesion between ink and substrate. However, since the national standard test method does not focus on the ink that sticks off the tape (only the surface ink sticks off), but only focuses on the remaining adhered ink on the substrate, the above test method cannot actually characterize the internal adhesion of the ink. In the actual test process, it often happens that a thin layer of ink on the tape is adhered off, but most of the ink is still retained on the substrate. Therefore, when calculating the adhesion data, this area is still considered to be the part that has not been peeled off.

[0008] Therefore, according to the national standard test method, the ink adhesion data measured is relatively high, but if the ink adhesion data is calculated based on the ink stuck on the tape, it is often lower. For the packaging of high-end tobacco, high-end cosmetics, high-end alcohol, etc., this problem is unacceptable.

[0009] Therefore, a water-based ink is needed that has good adhesion not only to a dedicated printing substrate but also to its own interior. Summary of the invention

[0010] In order to ensure that the water-based ink has good adhesion not only to the printing substrate but also to the inside of the ink itself, the present application provides a water-based ink with high adhesion and a preparation process thereof.

[0011] In a first aspect, the present application provides a water-based ink with high adhesion, using the following technical solution: A water-based ink with high adhesion, comprising at least the following raw materials in parts by weight: Acrylic emulsion 100-140 parts; 120-160 parts of titanium dioxide; 20-60 parts of ethylene glycol; Functional additives 0-5 parts; 80-100 parts of organic pigment; 400-600 parts of deionized water; Porous cellulose is also added to the water-based ink, the added mass of the porous cellulose is 0.08-0.16 times the sum of the mass of the acrylic emulsion and the titanium dioxide, and the Zeta potential of the porous cellulose at pH=7 is not greater than -45mV; the porous cellulose is obtained by dissolving cellulose diacetate, solidifying and separating the phases, and hydrolyzing and regenerating the cellulose in a hydrolysis bath, the hydrolysis bath is an aqueous solution of sodium hydroxide and a potential regulator, and the potential regulator is at least one of triethylamine, diethylamine, and ammonia water.

[0012] By adopting the above technical solution, the large number of hydroxyl groups on the surface of the porous cellulose added in this application endows it with good hydrophilicity, which enables it to be evenly dispersed, and the evenly dispersed regenerated cellulose can generate a large number of hydrogen bonds with the water-based resin (acrylic emulsion) and titanium dioxide filler in the ink. And its addition amount is not less than 0.08 times the sum of the mass of acrylic emulsion and titanium dioxide. Therefore, the addition of porous cellulose means that a large number of introduced hydrogen bonds can form a relatively complete hydrogen bond network, thereby improving the tight connection properties of the various components of the paint film.

[0013] In addition, it is a common method to add thin and long fibers to water-based ink to improve the strength of the paint film. However, what is added in this application is not thin and long cellulose fibers, but porous cellulose with a large number of microporous structures.

[0014] Compared with the addition of slender cellulose fibers, the porous cellulose with irregular shapes in the present application can make the paint film have better strength and significantly higher adhesion. On the one hand, compared with natural cellulose in nature, a large number of microporous structures will be introduced in the phase separation and regeneration process of regenerated cellulose, and these microporous structures will produce obvious capillary phenomena. Therefore, the paint film finally formed will have a large amount of water-based resin and other components embedded in the microporous structure of porous cellulose, forming a physical mosaic in addition to the hydrogen bond network, which greatly improves the compatibility and connection tightness of the materials in the paint film, which greatly improves the peeling strength of the paint film. It is worth noting that the so-called high peeling strength is not only the paint film and the substrate, but more importantly, the paint film is tightly bonded, so it is not easy to be peeled off.

[0015] Of course, the amount of porous cellulose added is not suitable to be higher than 0.16 times, so as to avoid excessive introduction of hydroxyl groups which significantly increase the hydrophilicity of the paint film, thereby causing the paint film to have excessive hydrophilic and hygroscopic properties, which in turn reduces the tightness of the connection between the materials in the paint film. In addition, the microporous structure of porous cellulose will not only produce capillary adsorption of materials in the paint film, but also lead to capillary water absorption. Therefore, if the amount of porous cellulose added is too large, in addition to the excessive introduction of hydroxyl groups, the capillary water absorption brought about by the excessive microporous structure will also lead to the problem of decreased adhesion of the paint film due to increased water absorption.

[0016] In addition, the inventors of this application unexpectedly discovered that by adding a negatively charged cellulose with a Zeta potential of no more than -45mV (an absolute value of no less than 45mV), the final paint film can have higher strength and significantly better adhesion. This result is very different from conventional cognition. It is generally believed that for cellulose materials, the higher the crystallinity of cellulose, the higher the strength. After adding it to the ink, the paint film can obtain higher strength and adhesion between the paint films, thereby avoiding peeling (strong anti-peeling performance). This is because the negative charge carried by porous cellulose is generally caused by the ionization of the hydroxyl groups it carries. Since the crystalline region of porous cellulose forms highly ordered intermolecular and intramolecular hydrogen bonds, it is difficult to ionize. Only the free hydroxyl groups in the amorphous region that do not form intermolecular and intramolecular hydrogen bonds will ionize and show electronegativity, which makes the cellulose with higher crystallinity often have a smaller absolute value of Zeta potential. Therefore, in order to obtain a paint film with higher strength and higher anti-peeling ability, it should be preferred to add cellulose with high crystallinity, which naturally means that cellulose with a relatively small absolute value of Zeta potential should be preferred.

[0017] However, the inventors of the present application found that by adding porous cellulose with negative charge and relatively large absolute value of Zeta potential, a paint film with better anti-stripping performance and strength can be obtained, which is quite unexpected. As mentioned above, a large absolute value of Zeta potential often means that the porous cellulose has lower crystallinity and lower strength, and the addition of porous cellulose with lower strength actually has higher anti-stripping performance and paint film strength, which is quite unexpected.

[0018] This may be due to the fact that, in the hydrolysis and regeneration process of the porous cellulose in the present application, on the basis of the addition of sodium hydroxide, at least one of triethylamine, diethylamine and ammonia is further added as a potential regulator, and these potential regulators are all alkaline. On the one hand, the potential regulator can further provide alkaline hydrolysis conditions, and more importantly, by adding at least one of triethylamine, diethylamine and ammonia in the hydrolysis bath, the porous cellulose obtained by hydrolysis can be provided with a larger amount of negative charge, which is manifested as an increase in the absolute value of its Zeta potential. In the hydrolysis and regeneration process, the ester bond on the cellulose diacetate is hydrolyzed so that the acetate group falls off and the hydroxyl group is reintroduced. For the hydrogen bonds in the crystalline region, since the potential regulator is difficult to enter, the hydroxyl groups in the crystalline region are less disturbed and will regenerate intermolecular and intramolecular hydrogen bonds to ensure a higher degree of crystallinity; and for the hydroxyl groups in the amorphous region, the potential regulator forms hydrogen bonds with the reintroduced hydroxyl groups, thereby greatly reducing the intermolecular and intramolecular hydrogen bonds in the amorphous region and increasing the amount of free hydroxyl groups. Compared with the hydroxyl groups in the crystalline region, the hydroxyl groups in the amorphous region are significantly more accessible and more easily ionized to be electronegative. Therefore, the addition of the potential regulator can reduce the formation of hydrogen bonds between and within the amorphous region molecules while having little effect on the crystalline region of the porous cellulose, thereby obtaining a larger absolute value of the Zeta potential. A larger absolute value of the Zeta potential means, on the one hand, that the porous cellulose is more evenly dispersed in the water-based ink due to greater electrostatic repulsion, and on the other hand, that more free hydroxyl groups can form hydrogen bonds with water-based resins and titanium dioxide, thereby greatly improving the integrity of the hydrogen bond network formed, which can greatly improve the strength of the final paint film and the firmness of the connection between the materials in the paint film, thereby greatly improving the anti-peeling performance of the paint film.

[0019] In summary, porous cellulose with a large number of free hydroxyl groups can be prepared by adding a potential regulator to the hydrolysis bath, and porous cellulose with good hydrophilicity, a large number of negative charges and a large number of microporous structures (Zeta potential is not greater than -45mV) is added, and its addition amount is controlled to 0.08-0.16 times the sum of the mass of acrylic emulsion and titanium dioxide, so that the final paint film has significantly better adhesion between paint films.

[0020] Optionally, the Zeta potential of the porous cellulose is not less than -85 mV, and the added mass of the porous cellulose is 0.1-0.14 times the sum of the mass of the acrylic emulsion and the titanium dioxide.

[0021] By adopting the above technical solution, of course, the charge carried by the porous cellulose should not be excessive (the absolute value should not be greater than 85mV). This is because when diacetate cellulose is hydrolyzed and regenerated in a hydrolysis bath, the amorphous region can provide limited free hydroxyl groups. Therefore, if the absolute value of the Zeta potential of the porous cellulose is greater than 85mV, it means that the porous cellulose crystalline region finally obtained is greatly affected and becomes an amorphous region. At this time, although there are indeed more free hydroxyl groups, the strength of the porous cellulose itself will be significantly reduced, resulting in a decrease in the strength and anti-peeling properties of the final paint film.

[0022] Optionally, the concentration of sodium hydroxide in the hydrolysis bath is 0.2-1 g / L, the concentration of the potential regulator is 0.05-0.1 g / L, and the potential regulator is a mixture of triethylamine and ammonia water in a mass ratio of 1:2-3.

[0023] By adopting the above technical solution, the concentration of the potential regulator should not be too low or too high. If the concentration of the potential regulator is too high, it is likely to form an undesirable interference with the construction of intermolecular and intramolecular hydrogen bonds in the crystalline region during the hydrolysis and regeneration of cellulose acetate and the reintroduction of hydroxyl groups, thereby causing the crystallinity of the porous cellulose obtained to be excessively reduced, making it difficult to play a good strengthening and anti-peeling role in the paint film. If the concentration of the potential regulator is too low, it is likely to be difficult to prevent the formation of intermolecular and intramolecular hydrogen bonds in the amorphous region of the porous cellulose, and the number of free hydroxyl groups will decrease. Since the amount of porous cellulose added in this application is small, it is difficult for the hydrogen bonds formed based on the porous cellulose to form a complete network, and it is naturally difficult to play a good anti-peeling ability.

[0024] In addition, the inventors of the present application have found that, compared to the addition of triethylamine, diethylamine or ammonia water alone, the use of triethylamine and ammonia water as a potential regulator can make the porous cellulose finally obtained obtain a larger absolute value of Zeta potential at the same addition amount. This may be due to the fact that, compared to triethylamine and diethylamine, the permeability of ammonia water is significantly stronger, and it is easier to enter the amorphous region of cellulose, and compared to diethylamine and ammonia water, triethylamine has a stronger alkalinity and has the effect of forming hydrogen bonds, so it is easier to cooperate with sodium hydroxide to attack the ester group on the amorphous region, prompting the acetate group to fall off and reintroduce the hydroxyl group. Therefore, triethylamine promotes hydrolysis with ammonia water that is highly permeable and easy to produce hydrogen bonds, which can make the amorphous region more prone to hydrolysis and regeneration and reduce the possibility of intermolecular and intramolecular hydrogen bonds in the amorphous region of cellulose, so as to obtain the porous cellulose with the desired large absolute value of Zeta potential.

[0025] Optionally, 5-15 parts by weight of a thickener is further added to the aqueous ink, and the thickener is a mixture of sodium alginate and sodium carboxymethyl cellulose in a mass ratio of 1-2:1.

[0026] By adopting the above technical scheme, sodium alginate and sodium carboxymethyl cellulose are both common thickeners for water-based inks, and the combination of the two can play a good thickening and stabilizing role. Among them, sodium carboxymethyl cellulose is a natural polymer compound soluble in water with good thickening properties. Sodium alginate is a polysaccharide extracted from brown algae seaweed, which has excellent gelling ability and stability. By combining these two functional substances, the comprehensive performance of sodium carboxymethyl cellulose plus sodium alginate has been further improved. Stability is also one of the key properties of many products. Sodium carboxymethyl cellulose plus sodium alginate can effectively prevent the sedimentation and aggregation of solid particles or bubbles in liquid and gel systems. Its excellent stability enables the product to remain stable for a long time during storage, transportation and use, and is not easy to stratify and precipitate. This is very important for water-based ink systems with titanium dioxide inorganic particles added.

[0027] Optionally, the thickener is added by first blending it with the porous cellulose and then adding it to the aqueous ink.

[0028] By adopting the above technical solution, the inventors of the present application found that if the thickener is directly added to the water-based ink, the water-based ink is prone to stratification. This may be because the thickener will combine with the titanium dioxide, which has a high surface energy and has the orientation of agglomerating with each other to reduce the surface energy. Once the titanium dioxide and the thickener agglomerate with each other, undesirable sedimentation and stratification problems will occur.

[0029] In particular, the uniform addition of thickeners has always been a difficult technical problem to solve. The thickeners are often added in local excess, so the local viscosity is too high, and it is easier to react with fillers such as titanium dioxide to form uncontrollable agglomerated particles. During long-term storage, these agglomerated particles will cause stratification, and after the paint film is formed, these agglomerated particles will become defects. Once there are defects in the paint film, its local anti-peeling performance will decrease.

[0030] In order to solve this problem, the thickener is added in the present application in a manner that is first blended with porous cellulose to be adsorbed into the porous microporous structure of the porous cellulose, so that when added to the water-based ink, the thickener located in the porous cellulose will be slowly released, and this slowly released thickener greatly improves the uniformity of thickener addition; and, as mentioned above, the porous cellulose added in the present application carries a large amount of charge, which not only enables itself to have good dispersion uniformity, but also greatly improves the dispersion uniformity of fillers such as titanium dioxide in the system. Therefore, the porous cellulose, which is already uniformly dispersed, makes the thickener located in the microporous structure and slowly released also uniformly distributed, and the uniform dispersion of the titanium dioxide filler brought about by the electrostatic repulsion of the porous cellulose significantly reduces the possibility of local agglomerated particles, which on the one hand greatly reduces the stratification problem caused by the agglomerated particles, and on the other hand greatly alleviates the problem of decreased anti-peeling performance of the paint film due to uneven addition of the thickener.

[0031] Optionally, inorganic particles are embedded in the porous cellulose, and the inorganic particles include zirconium oxide and zinc oxide. The mass ratio of the inorganic particles to the regenerated cellulose is 1:10-20.

[0032] By adopting the above technical solution, it is worth noting that when the thickener contains sodium alginate, whether the porous cellulose is embedded with inorganic particles of zirconium oxide and zinc oxide has an unexpectedly significant effect on the anti-stratification and anti-stripping properties of the water-based ink. Specifically, the inventors of the present application found in a control experiment that if inorganic particles are not added to the porous cellulose, the anti-stratification and anti-stripping properties of the water-based ink are significantly reduced, which is quite unexpected. It is generally believed that the inorganic particles embedded in the porous cellulose will not affect the anti-stratification and anti-stripping properties of the water-based ink.

[0033] This may be because, although sodium alginate can be used to adjust the viscosity of the system, the molecular chain of sodium alginate is unstable and is prone to degradation during the production process at slightly higher temperatures or during high-temperature storage, which leads to unexpected changes in the viscosity of the water-based ink and a decrease in the anti-stratification performance of the water-based ink. Similar to sodium alginate, it is difficult to avoid a certain degree of heating during the production process of water-based inks, and acrylic emulsion is an alkali-soluble resin, so the entire system is alkaline and the temperature is relatively high. Under these conditions, regenerated cellulose is prone to uncontrollable degradation.

[0034] Zinc oxide is a commonly used whitening agent, which has a good whitening effect in water-based inks. In addition, zinc oxide can also be used as a catalyst to promote the curing reaction of water-based inks. This is very helpful for improving the printing speed and printing effect of water-based inks. The zirconium oxide embedded in the porous cellulose has a good thermal insulation effect, which can not only avoid the high-temperature alkaline hydrolysis of regenerated cellulose, but also significantly reduce the degradation process of sodium alginate, thereby alleviating the adverse effects caused by the hydrolysis or degradation of the two. Therefore, the curing-promoting effect of zinc oxide can, on the one hand, avoid the problems of film adhesion and water resistance caused by insufficient ink curing and drying speed, and on the other hand, it can appropriately reduce the high-temperature drying and curing time of water-based inks, and the good thermal insulation effect of zirconium oxide can produce high-temperature alkaline hydrolysis of porous cellulose. The synergistic cooperation of the two can keep the porous cellulose in good performance, so that the paint film has better anti-peeling properties.

[0035] In addition, as mentioned above, compared with natural cellulose, regenerated cellulose exhibits significantly stronger capillary water absorption due to its microporous structure, and the inorganic particles filled in the microporous structure can alleviate this phenomenon to a certain extent; on the other hand, the texture of regenerated cellulose is relatively soft, and the embedded inorganic particles can significantly increase the strength of cellulose, so that the cellulose dispersed in the paint film plays a good pinning role. Overall, the embedded inorganic particles can reduce capillary water absorption, and more positive effects of the hydrogen bonds formed by cellulose itself on water resistance are shown, which can also improve the anti-peeling performance of the paint film.

[0036] Optionally, the inorganic particles are a mixture of zirconium oxide and zinc oxide in a mass ratio of 3-5:1.

[0037] By adopting the above technical solution, the high absolute value of the Zeta potential of the porous cellulose means that zinc oxide and zirconium oxide are uniformly dispersed along with the uniform dispersion of the porous cellulose, which greatly avoids the problem of paint film defects caused by excessive local viscosity and uneven curing due to local enrichment of inorganic particles.

[0038] On this basis, the amount of zirconium oxide added is controlled to be 3-5 times that of zinc oxide, because zinc oxide has a slightly greater effect on the viscosity of water-based ink. In order to avoid an unexpected increase in the viscosity of the water-based ink and to avoid excessive local zinc oxide causing the water-based ink that penetrates into the porous cellulose and around the porous cellulose to solidify too quickly, which in turn brings about unexpected paint film problems, therefore, zinc oxide is preferably added in a small amount.

[0039] Optionally, the porous cellulose is prepared by the following process: A1. Dispersing inorganic particles, placing the inorganic particles in a solvent and ultrasonically dispersing them to obtain a dispersion, wherein the solvent is at least one of acetone, dioxane, dimethylacetamide, and N-methylpyrrolidone; A2, dissolving, adding cellulose diacetate into the dispersion and dissolving to obtain a blended liquid, wherein the added concentration of cellulose diacetate is 8-12wt%, and the mass ratio of the inorganic particles to the regenerated cellulose is 1:10-20; A3, phase separation solidification, placing the blended liquid in a phase separation bath, making the cellulose diacetate phase separate into a microporous structure and making the inorganic particles adhere to the fibers, filtering out to obtain a semi-finished product, wherein the phase separation bath is an aqueous solution of a small molecule alcohol, the surface tension of the phase separation bath is not more than 40 mN / m, and the small molecule alcohol is at least one of ethanol, propanol, and isopropanol; A4, hydrolysis regeneration, the semi-finished product is mixed with a hydrolysis bath to hydrolyze the cellulose diacetate to remove the acetate group and regenerate cellulose, the hydrolysis bath is an aqueous solution of sodium hydroxide and a potential regulator, the potential regulator is at least one of triethylamine, diethylamine, and ammonia water, after the hydrolysis is completed, the cellulose is filtered out and washed to obtain porous cellulose.

[0040] By adopting the above technical solution, in step A3, the phase separation bath with low surface tension can improve its penetration ability, so as to more quickly exchange with the solvent in the blend liquid to form micropores with smaller pore sizes, and the lower concentration of cellulose diacetate makes the pores smaller but more numerous. Therefore, the phase separation bath with low surface tension can make the final regenerated cellulose have a large number of small-sized microporous structures, so that after adding water-based ink, a better physical mosaic effect can be formed, and it is easier to form a hydrogen bond network through more evenly dispersed and exposed hydroxyl groups, thereby improving water resistance and anti-stratification performance.

[0041] The role of the potential regulator in step A4 is as described above and will not be repeated here.

[0042] Optionally, the step A4 specifically includes the following steps: A41, cold mixing, blending the semi-finished product with the hydrolysis bath, and controlling the system temperature to be no greater than 20° C. to obtain a cold mixing system; A42, heating and hydrolysis, heating the cold mixed system to 60-80°C to hydrolyze the cellulose diacetate under alkaline conditions to regenerate the cellulose; A43. Filtration and washing: the regenerated cellulose in the hydrolysis system and the inorganic particles embedded in the micropores of the regenerated cellulose are filtered and washed to neutrality to obtain porous cellulose.

[0043] By adopting the above technical solution, compared with directly mixing the semi-finished product with sodium hydroxide solution under high temperature conditions for hydrolysis and regeneration, the method of cold mixing first and then heating for hydrolysis is adopted, which can ensure that the sodium hydroxide is first evenly attached to the fiber and then hydrolyzed, thereby improving the hydrolysis uniformity of cellulose diacetate, and accordingly, can improve the defect resistance of water-based ink.

[0044] In a second aspect, the present application provides a process for preparing a water-based ink, which adopts the following technical solution: A preparation process of a water-based ink comprises the following process steps: S1, thickening and blending, preparing a thickener into an aqueous solution at a concentration of 3-5 wt%, then blending it evenly with the porous cellulose, and drying the blend to allow the thickener to adhere to the porous cellulose; S2, stirring and preliminarily mixing, blending and uniformly mixing all the raw materials except the acrylic emulsion and the porous cellulose, and then adding the acrylic emulsion and stirring uniformly to obtain a preliminarily mixed material; S3, sand grinding, transferring the primary mixture to a sand mill for a first-stage sand grinding, then adding porous cellulose for a second-stage sand grinding, filtering and discharging the material after the sand grinding is completed; in the first-stage grinding, the cooling water is indirectly cooled to control the grinding temperature to 25-35° C., and the first-stage grinding is completed when the fineness is not greater than 15 μm; then the cooling water is cut off and porous cellulose with thickener attached is added, and the grinding state is maintained until the temperature in the grinder reaches 50-60° C., and the second-stage grinding is completed; S4. Packaging, storage and transportation.

[0045] By adopting the above technical solution, a special two-stage grinding method can ensure a good grinding effect by first performing a high-viscosity grinding at a low temperature, and further adding porous cellulose and grinding at a high temperature with low viscosity. On the one hand, it can avoid the problems of difficulty in discharging and clogging of the sand mill due to high viscosity, and on the other hand, it can avoid the excessive sand grinding and crushing of the softer regenerated cellulose, which makes it difficult to play the role of local pinning and physical interlocking. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 It is a SEM picture of typical porous cellulose prepared in this application. DETAILED DESCRIPTION

[0047] The present application is described in further detail below.

[0048] The following is an example of preparing porous cellulose disclosed in this application: Preparation Example 1 The porous cellulose in this preparation example is prepared by the following process steps: A1. Dispersion of inorganic particles: Inorganic particles are placed in a solvent and ultrasonically dispersed to obtain a dispersion. The solvent is N-methylpyrrolidone. The total concentration of inorganic particles added is controlled to be 0.67wt%. In this preparation example, the inorganic particles are a mixture of zirconium oxide and zinc oxide in a mass ratio of 4:1. The ultrasonic dispersion process only needs to ensure that the inorganic particles are fully dispersed, and conventional adjustments can be made. In this preparation example, the ultrasonic power is 50W, the ultrasonic time is 15min, and the zirconium oxide is purchased from DKK Company (Daiichi Rare Element Chemical Industry Co., Ltd.) of Japan. The specific model is UEP-50. 50 The surface area is 0.07-0.27 μm and the specific surface area is 40-60 m 2 / g; zinc oxide is DXN-ZY06 from Chaotai Metal Materials, with a primary particle size of about 200-300nm and a specific surface area of ​​more than 5m 2 / g.

[0049] A2. Dissolving: adding cellulose diacetate to the dispersion and dissolving to obtain a blended liquid, wherein the added concentration of cellulose diacetate is 10wt%; in the blended liquid, the added mass ratio of inorganic particles to cellulose diacetate is 1:15; cellulose diacetate is purchased from Daicel Corporation, and the specific model is CAFBLO® Flake L-50, and its esterification rate (acetic acid binding rate, acetylation degree) is 54%-56%.

[0050] A3, phase separation solidification, injecting the blended liquid into the stirring phase separation bath by spraying through a nozzle, so that the diacetate cellulose is phase-separated into a microporous structure and the zirconium oxide is attached to the fiber, and the semi-finished product is obtained by filtering, and the phase separation bath is an aqueous solution of small molecule alcohol. In this preparation example, the phase separation bath is an aqueous solution of ethanol, and the surface tension of the phase separation bath is about 35mN / m by controlling the concentration of ethanol; the injection speed of the blended liquid is 6L / min, and the stirring speed of the phase separation bath is 75r / min.

[0051] A4, hydrolysis regeneration, the semi-finished product is mixed with a hydrolysis bath to hydrolyze the cellulose diacetate to remove the acetate group and regenerate cellulose, and the regenerated cellulose with inorganic particles embedded therein is obtained by filtering and washing; specifically, this step adopts a process of cold mixing first and then hot hydrolysis, and the specific steps are as follows: A41, cold mixing, blending the semi-finished product with the hydrolysis bath, and controlling the system temperature to be no more than 20°C, specifically, in this preparation example, the system temperature is controlled to be 15°C to obtain a cold mixing system; the hydrolysis bath is an aqueous solution of sodium hydroxide and a potential regulator, wherein the concentration of the sodium hydroxide solution is controlled to be 0.5g / L, and the total concentration of the potential regulator is controlled to be 0.075wt%, specifically, the potential regulator is a mixture of triethylamine and ammonia water in a mass ratio of 1:2.5, and the concentration of ammonia water used in this preparation example is 25%; in step A2 of this preparation example, a total of 50g of cellulose diacetate is used, therefore, in this step, the total amount of sodium hydroxide added is controlled to be 20g, and since the concentration of the sodium hydroxide solution is controlled to be 0.5g / L, a total of 40L of sodium hydroxide solution is required to ensure that the ratio of the mass of sodium hydroxide in the sodium hydroxide solution to the mass of cellulose diacetate added in step A2 is 1:2.5.

[0052] A42, heating and hydrolysis, heating the cold mixed system to 70°C to hydrolyze the cellulose diacetate under alkaline conditions to regenerate the cellulose into regenerated cellulose; A43, filtering and washing, filtering and washing the regenerated cellulose in the hydrolysis system and the zirconium oxide embedded in the micropores of the regenerated cellulose until neutral, so as to obtain porous cellulose; the scanning electron microscope image of the obtained porous cellulose is as follows Figure 1 The zeta potential of the porous fiber prepared in this preparation example was measured to be -66 mV at pH = 7.

[0053] Preparation Example 2-7 The main difference between Preparation Example 2-7 and Preparation Example 1 is that each preparation process step is appropriately adjusted, as shown in the following table for details:

[0054] Specifically, the difference between Preparation Example 2 and Preparation Example 1 is mainly in the adjustment of components and process parameters, and the mass ratio of zirconium oxide to zinc oxide in the inorganic particles is controlled to be 3:1, and the mass ratio of triethylamine to ammonia in the potential regulator is controlled to be 1:2. The difference between Preparation Example 3 and Preparation Example 1 is mainly in the adjustment of components and process parameters, and the mass ratio of zirconium oxide to zinc oxide in the inorganic particles is controlled to be 5:1, and the mass ratio of triethylamine to ammonia in the potential regulator is controlled to be 1:3.

[0055] The main difference between Preparation Example 4 and Preparation Example 1 is that the inorganic particles used are only zirconium oxide without adding zinc oxide. The main difference between Preparation Example 5 and Preparation Example 1 is that the inorganic particles used are only zinc oxide without adding zirconium oxide.

[0056] In Preparation Example 6, no inorganic particles were added.

[0057] The main difference between Preparation Example 7 and Preparation Example 1 is that, on the basis of the total added mass of inorganic particles remaining unchanged, the mass ratio of zirconium oxide to zinc oxide in the inorganic particles is controlled to be 1:1.

[0058] The main difference between Preparation Examples 8-12 and Preparation Example 1 is that, on the basis of keeping the amount of potential regulator added unchanged, the type and compounding method of the potential regulator are adjusted to confirm the effect of different compounding methods on the Zeta potential of the prepared porous cellulose.

[0059] The main difference between Preparation Example 13 and Preparation Example 1 is that a slightly excessive amount of the potential adjuster is added.

[0060] The main difference between Preparation Example 14 and Preparation Example 1 is that no potential regulator is added during the hydrolysis regeneration process.

[0061] The following are examples of water-based inks disclosed in this application: Example 1: This application example discloses a water-based ink with high adhesion. The water-based ink with high adhesion specifically includes the following raw materials in parts by weight: Acrylic emulsion 120 parts; 140 parts of titanium dioxide; Thickener 10 parts; 3 parts of functional additives; 90 parts of organic pigment; 40 parts of ethylene glycol; 500 parts of deionized water; 31.2 parts of porous cellulose is 0.12 times the sum of the added mass of acrylic emulsion and titanium dioxide.

[0062] Specifically, the acrylic emulsion in this embodiment is purchased from Dow Chemical's RESIN HF-05A water-based self-crosslinking thermosetting acrylic resin, and its solid content is about 40%; the titanium dioxide is specifically Bluestar Dahua's anatase titanium dioxide DHA-100, and the thickener is a mixture of sodium alginate and sodium carboxymethyl cellulose in a mass ratio of 1.5:1; the functional additive is specifically 1 part of defoaming agent to 2 parts of leveling agent, the defoaming agent is specifically Dow Chemical's DC65 silicone defoaming agent, and the leveling agent is specifically BYK-333 silicone leveling agent; the organic pigment can be selected conventionally, and in this embodiment, the organic pigment is phthalocyanine blue BGS.

[0063] The high-adhesion water-based ink in this embodiment is prepared by the following process steps: S1. Thickening and blending: the thickener is prepared into an aqueous solution at a concentration of 4wt%, and then evenly blended with the porous cellulose. The blend is dried to allow the thickener to adhere to the porous cellulose. It should be noted that the concentration of the thickener only needs to ensure that it can be well dispersed without obvious agglomeration. Of course, in order to avoid excessive energy waste during the drying process, the thickener concentration should not be too high. Overall, preparing the thickener solution within a reasonable range has no substantial effect on the final performance.

[0064] S2, stirring and preliminarily mixing, blending and uniformly mixing all the raw materials except the acrylic emulsion and the porous cellulose, and then adding the acrylic emulsion and stirring uniformly to obtain a preliminarily mixed material.

[0065] S3, sand grinding, transferring the primary mixture to a sand mill for a first-stage sand grinding, then adding porous cellulose for a second-stage sand grinding, filtering and discharging the material after the sand grinding is completed; in the first-stage grinding, the cooling water is indirectly cooled to control the grinding temperature to 30°C, and the first-stage grinding is completed when the fineness is not greater than 15 μm; then the cooling water is cut off and porous cellulose with thickener attached is added, and the grinding state is maintained until the temperature in the grinder reaches 55°C, completing the second-stage grinding; S4. Packaging, storage and transportation.

[0066] Example 2-16: The main difference between Example 2-16 and Example 1 is that the raw material source, ratio and process parameters are slightly adjusted, as shown in the table below.

[0067] Specifically, the main difference between Example 2 and Example 3 and Example 1 is that the ink formula and process are adjusted.

[0068] The main difference between Example 4 and Example 1 is that the porous cellulose prepared in Preparation Example 1 in Example 1 is replaced by the porous cellulose prepared in Preparation Example 13 of equal mass.

[0069] The main difference between Example 5 and Example 1 is that the porous cellulose prepared in Preparation Example 1 in Example 1 is replaced by the porous cellulose prepared in Preparation Example 8 of equal mass.

[0070] The main difference between Example 6 and Example 1 is that the porous cellulose prepared in Preparation Example 1 in Example 1 is replaced by the porous cellulose prepared in Preparation Example 9 of equal mass.

[0071] The main difference between Example 7 and Example 1 is that the porous cellulose prepared in Preparation Example 1 in Example 1 is replaced by the porous cellulose prepared in Preparation Example 10 of equal mass.

[0072] The main difference between Example 8 and Example 1 is that the porous cellulose prepared in Preparation Example 1 in Example 1 is replaced by the porous cellulose prepared in Preparation Example 11 of equal mass.

[0073] The main difference between Example 9 and Example 1 is that the porous cellulose prepared in Preparation Example 1 in Example 1 is replaced by the porous cellulose prepared in Preparation Example 12 of equal mass.

[0074] The main difference between Example 10 and Example 1 is that the thickener is not first blended with the porous cellulose and then added, that is, in Example 10, step S1 is not performed, but the thickener is directly added and blended in step S2.

[0075] The main difference between Example 11 and Example 1 is that the porous cellulose prepared in Preparation Example 1 in Example 1 is replaced by the porous cellulose prepared in Preparation Example 7 of equal mass.

[0076] The main difference between Example 12 and Example 1 is that the porous cellulose prepared in Preparation Example 1 in Example 1 is replaced by the porous cellulose prepared in Preparation Example 6 of equal mass.

[0077] The main difference between Example 13 and Example 1 is that the porous cellulose prepared in Preparation Example 1 in the original Example 1 is simply replaced by the porous cellulose prepared in Preparation Example 5 of equal mass.

[0078] The main difference between Example 14 and Example 1 is that the porous cellulose prepared in Preparation Example 1 in the original Example 1 is simply replaced by the porous cellulose prepared in Preparation Example 4 of equal mass.

[0079] The main difference between Example 15 and Example 1 is that the porous cellulose prepared in Preparation Example 1 in the original Example 1 is simply replaced by the porous cellulose prepared in Preparation Example 3 of equal mass.

[0080] The main difference between Example 16 and Example 1 is that the porous cellulose prepared in Preparation Example 1 in the original Example 1 is simply replaced by the porous cellulose prepared in Preparation Example 2 of equal mass.

[0081] Comparative Example Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that the porous cellulose used in Comparative Example 1 is not the porous cellulose prepared in each preparation example of the present application, but conventional commercially available microcrystalline cellulose, specifically Toncellus® TC105 of Dongchen Pharmaceutical, whose D 50 The thickness is 20 μm and the bulk density is about 0.25 g / cm 3 .

[0082] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that a smaller amount of porous cellulose is added in Comparative Example 2. Specifically, the amount of porous cellulose added is 5.2 parts, which is 0.02 times the sum of the added masses of acrylic emulsion and titanium dioxide.

[0083] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, excessive porous cellulose is added, and the added amount is 65 parts, which is 0.25 times the sum of the added masses of acrylic emulsion and titanium dioxide.

[0084] Comparative Example 4 The only difference between Comparative Example 4 and Example 1 is that the porous cellulose added in Comparative Example 4 is the porous cellulose prepared in Preparation Example 14 without adding a potential regulator;

[0085] Performance testing and data Adhesion test method The water resistance of the aqueous ink prepared in each embodiment and comparative example of the present application is tested in accordance with the provisions of the standard GB / T 13217.7-2023 ink adhesion test method. It should be noted that in this test method, instead of covering the substrate with translucent millimeter grid paper, the tape is covered with translucent millimeter grid paper, and the number of grids occupied by the peeled ink layer and the total number of grids are counted, expressed in %. The larger the value, the worse the adhesion and the worse the anti-peeling performance. This test method not only requires that the paint film is not completely peeled off, but even if the surface layer is peeled off, it will be counted, so it can better show the anti-peeling performance of the paint film;

[0086] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

Claims

1. A water-based ink with high adhesion, characterized in that: At least the following raw materials by weight: Acrylic emulsion 100-140 parts; 120-160 parts of titanium dioxide; 20-60 parts of ethylene glycol; Functional additives 0-5 parts; 80-100 parts of organic pigment; 400-600 parts of deionized water; Porous cellulose is also added to the water-based ink, the added mass of the porous cellulose is 0.08-0.16 times the sum of the mass of the acrylic emulsion and the titanium dioxide, and the Zeta potential of the porous cellulose at pH=7 is not greater than -45mV; the porous cellulose is obtained by dissolving cellulose diacetate, solidifying and separating the phases, and hydrolyzing and regenerating the cellulose in a hydrolysis bath, the hydrolysis bath is an aqueous solution of sodium hydroxide and a potential regulator, and the potential regulator is at least one of triethylamine, diethylamine, and ammonia water.

2. The high-adhesion water-based ink according to claim 1, characterized in that: The Zeta potential of the multi-resistant cellulose is not less than -85 mV, and the added mass of the porous cellulose is 0.1-0.14 times the sum of the mass of the acrylic emulsion and the titanium dioxide.

3. The high-adhesion water-based ink according to claim 1, characterized in that: The concentration of sodium hydroxide in the hydrolysis bath is 0.2-1 g / L, the concentration of the potential regulator is 0.05-0.1 g / L, and the potential regulator is a mixture of triethylamine and ammonia water in a mass ratio of 1:2-3.

4. The high-adhesion water-based ink according to claim 1, characterized in that: The water-based ink is further added with 5-15 parts by weight of a thickener, which is a mixture of sodium alginate and sodium carboxymethyl cellulose in a mass ratio of 1-2:

1.

5. The high-adhesion water-based ink according to claim 4, characterized in that: The thickener is added in the following manner: firstly blended with the porous cellulose and then added into the water-based ink.

6. The high-adhesion water-based ink according to claim 1, characterized in that: Inorganic particles are also embedded in the porous cellulose. The inorganic particles include zirconium oxide and zinc oxide. The mass ratio of the inorganic particles to the regenerated cellulose is 1:10-20.

7. The high-adhesion water-based ink according to claim 6, characterized in that: The inorganic particles are a mixture of zirconium oxide and zinc oxide in a mass ratio of 3-5:

1.

8. The high-adhesion water-based ink according to any one of claims 1 to 7, characterized in that: The porous cellulose is prepared by the following process: A1. Dispersing inorganic particles, placing the inorganic particles in a solvent and ultrasonically dispersing them to obtain a dispersion, wherein the solvent is at least one of acetone, dioxane, dimethylacetamide, and N-methylpyrrolidone; A2, dissolving, adding cellulose diacetate into the dispersion and dissolving to obtain a blended liquid, wherein the added concentration of cellulose diacetate is 8-12wt%, and the mass ratio of the inorganic particles to the regenerated cellulose is 1:10-20; A3, phase separation solidification, placing the blended liquid in a phase separation bath, making the cellulose diacetate phase separate into a microporous structure and making the inorganic particles adhere to the fibers, filtering out to obtain a semi-finished product, wherein the phase separation bath is an aqueous solution of a small molecule alcohol, the surface tension of the phase separation bath is not more than 40 mN / m, and the small molecule alcohol is at least one of ethanol, propanol, and isopropanol; A4, hydrolysis regeneration, the semi-finished product is mixed with a hydrolysis bath to hydrolyze the cellulose diacetate to remove the acetate group and regenerate cellulose, the hydrolysis bath is an aqueous solution of sodium hydroxide and a potential regulator, the potential regulator is at least one of triethylamine, diethylamine, and ammonia water, after the hydrolysis is completed, the cellulose is filtered out and washed to obtain porous cellulose.

9. The high-adhesion water-based ink according to claim 8, characterized in that: The step A4 specifically includes the following steps: A41, cold mixing, blending the semi-finished product with the hydrolysis bath, and controlling the system temperature to be no greater than 20° C. to obtain a cold mixing system; A42, heating and hydrolysis, heating the cold mixed system to 60-80°C to hydrolyze the cellulose diacetate under alkaline conditions to regenerate the cellulose; A43. Filtration and washing: the regenerated cellulose in the hydrolysis system and the inorganic particles embedded in the micropores of the regenerated cellulose are filtered and washed to neutrality to obtain porous cellulose.

10. The production process of the water-based ink according to any one of claims 1 to 9, characterized in that: The process steps include: S1, thickening and blending, preparing a thickener into an aqueous solution at a concentration of 3-5 wt%, then blending it evenly with the porous cellulose, and drying the blend to allow the thickener to adhere to the porous cellulose; S2, stirring and preliminarily mixing, blending and evenly mixing all the raw materials except the acrylic emulsion and the porous cellulose, and then adding the acrylic emulsion and stirring evenly to obtain a preliminarily mixed material; S3, sand milling, transferring the primary mixed material to a sand mill for a first stage of sand milling, then adding porous cellulose for a second stage of sand milling, and filtering the material after the sand milling is completed; During the first stage of grinding, the grinding temperature is controlled to 25-35°C by indirect cooling with cooling water, and the first stage of grinding is completed when the fineness is not greater than 15μm; Then, the cooling water is cut off and porous cellulose with thickener attached is added, and the grinding state is maintained until the temperature in the grinder reaches 50-60°C, completing the second stage grinding; S4. Packaging, storage and transportation.

Citation Information

Patent Citations

  • Aqueous UV base coat and preparation method thereof

    CN101967323A

  • Preparation methods of porous carbon fiber / metal oxide composite material and graphene-based conductive ink and application of graphene-based conductive ink in supercapacitor

    CN113470981A

  • Special non-cured rubber asphalt waterproof coating and preparation method thereof

    CN113789124A

  • Peelable ink composition for porous substrates

    EP3988622A1

  • Ink, bonding kit, bonding sheet, and method for producing bonding sheet

    JP2021130786A